Enzymatic and protein crystallization and structure study - Ching, Chi Bun (2010)
In this work, we aimed to develop practical techniques and theoretical basis for protein crystallization to improve the success rate to obtain protein crystals with good quality. The effects of ionic strength, liquid-liquid phase separation and different chemically modified solid surfaces/substrates on the nucleation of protein crystals were investigated. Micro-batch crystallization experiments were conducted to study the mechanism of nucleation of protein crystals. An optical microscope with a heating/cooling stage was applied to determine the liquid-liquid co-existence curve, measure the initial nucleation rate and observe the liquid-liquid phase separation and subsequent crystallization process. A model was proposed to correlate and predict the cloud point temperature as a function of lysozyme concentration at fixed salt concentrations. In this model, the Random Phase Approximation, in conjunction with a square-well potential, was modified by assuming the square-well depth to be temperature dependent. The modified model was found to predict the liquid-liquid co-existence curve very well. Micro-batch crystallization experiments were also conducted on the microscope glass slides that were treated with poly-L-glutamic acid (PLG), poly(2-hydroxyethyl methacrylate) (P2HEMA), poly(methyl methacrylate) (PMMA), poly(4-vinyl pyridine) (P4VP) and (3-aminopropyl)triethoxysilane (APTES). The induction time of heterogeneous nucleation was measured. The surface topography and roughness were characterized by atomic force microscope (AFM). Contact angles for crystallization solution on the investigated surfaces were measured by contact angle meter. Theoretical analysis and experimental results show that, the surface roughness and topography can remarkably affect the free energy required for the formation of critical nucleus. Furthermore, hydrophobicity, electrostatic and antibacterial property of surface also greatly affected protein nucleation.